Impediments to and impact of checklists on performance of emergency interventions in primary care: an in situ simulation-based randomized controlled trial - Eric Dryver; Jeanette Knutsson; Ulf Ekelund; Anders Bergenfelz (Taylor & Francis Group, 2021)
Objective Medical crises occur rather seldom in the primary care setting, but when they do, initial management impacts on morbidity and mortality. Factors that impede the performance of emergency interventions in primary care have not been studied through in-situ simulation. Checklists reportedly improve crisis management. Design This randomized controlled trial evaluated emergency intervention performance during two scenarios (hypoglycemia-coma and anaphylaxis-cardiac arrest) simulated at primary care centers, and whether checklist access improved performance. Setting Twenty-two primary care centers in Southern Sweden participated in the study. Subjects A total of 347 personnel performed 100 simulations, 45 with and 55 without checklist access. Main outcome measures Time and impediments to performance of five emergency interventions in each scenario. Results On 28 of the 37 occasions when the adrenalin auto-injector was employed, the administration technique was incorrect. In 9 of 49 scenarios, teams had trouble locating the 30% glucose solution. Median time to supplemental oxygen administration during the first scenario was 186 s compared with 96 s during the second scenario (p < 0.001). Checklist access had no significant impact on time to performance of emergency interventions, aside from shorter time to adequate glucose or glucagon administration (median times 632 s with, 756 s without checklist access; p = 0.03). Conclusion Unfamiliarity with local emergency equipment impedes the performance of emergency interventions during crises simulated in the primary care setting. Simply providing checklist access does not improve the performance of emergency interventions.KEY POINTS Little is known about the factors that affect the performance of emergency interventions in the primary care setting. Unfamiliarity with local emergency equipment impedes the performance of emergency interventions during crises simulated in the primary care setting. Simply providing crisis checklist access does not improve the performance of emergency interventions in the primary care setting.